2018
DOI: 10.4172/2161-1068.1000256
|View full text |Cite
|
Sign up to set email alerts
|

The Yield of Sputum Smear Direct Microscopy Using Ziehl-Neelsen Stain in Comparison with Lowenstein Jensen Culture on the Diagnosis of Pulmonary Tuberculosis in Tripoli-Libya

Abstract: Background:In the developing countries, Tuberculosis is one of leading causes of morbidity and mortality. The detection and identification of Mycobacterium tuberculosis is considered a great challenge for clinical microbiologists. Albeit Ziehl-Neelsen (ZN) smear is being a rapid diagnostic tool for TB, the culture on Lowenstein Jensen (LJ) medium is considered the golden diagnostic tool for TB in the developing countries.Objectives: To evaluate the validity and reliability of ZN smear of acid-fast bacilli comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The direct smear microscopy method applied frequently in the third world and particularly in Iraq, is one of the methods that can be used to diagnose tuberculosis. Regarding the diagnosis of tuberculosis, the LJ culture medium is usually recognized as the gold standard in underdeveloped nations 8 . In terms of the clinical manifestations that they cause, pulmonary tuberculosis (also known as PTB) and extra-pulmonary tuberculosis (also known as EPTB) are the two most frequent types of tuberculosis (TB).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct smear microscopy method applied frequently in the third world and particularly in Iraq, is one of the methods that can be used to diagnose tuberculosis. Regarding the diagnosis of tuberculosis, the LJ culture medium is usually recognized as the gold standard in underdeveloped nations 8 . In terms of the clinical manifestations that they cause, pulmonary tuberculosis (also known as PTB) and extra-pulmonary tuberculosis (also known as EPTB) are the two most frequent types of tuberculosis (TB).…”
Section: Discussionmentioning
confidence: 99%
“…Most droplets released from the mouth, nose, and throat when someone talks, or coughs transmit tuberculosis, a respiratory disease. However, tuberculosis can also spread to other body regions, such as the lymph nodes, pleura, belly and urogenital tract 3,4 , skin and joints 5,6 , bones 7,8 , and the meninges. Extra-pulmonary tuberculosis is the name given to the following type of illness.…”
Section: Introductionmentioning
confidence: 99%
“…This media is a synthetic medium that contains eggs and is enriched with glycerol and asparagine which can fertilize the growth of Mycobacterium tuberculosis (Daulay et al, 2015). In addition, LJ media is considered a superior diagnostic tool in developing countries (Shoukrie et al, 2018) and based on research conducted by Pestariati and Meilinda (2021), showed that LJ solid media has good performance in growing Mycobacterium tuberculosis bacteria in BTA positive microscopic samples.…”
Section: Activity Test As Anti Tuberculosismentioning
confidence: 99%